Effect of Tax Rate, Taxation Technology and Information, Possibility of Fraud Detection, and Tax Fairnesson Taxpayer Perception of Tax Fraud Ethics (Empirical Study on KPP Pekanbaru, Dumai, Rokan Hilir) - Meilda Wiguna; Eka Hariyani (Jurnal Akuntansi Keuangan dan Bisnis, 2018)
This research is aimed to examine effect of tax rate, taxation technology and information, possibility of fraud detection, and tax fairness on taxpayer perception of tax fraud ethics. This research uses primary data by questioners. Data are analyzed by using multiple regression with 105 respondents of individual taxpayers (wajib pajak orang pribadi) listed in Kantor Pelayanan Pajak  (KPP) Pratama Senapelan Pekanbaru, KPP Dumai Kota, KPP Rokan Hilir, Riau, Indonesia. Results show that tax rate has effect on taxpayer perception of tax fraud ethics, taxation technology and information has effect on taxpayer perception of tax fraud ethics, possibility of fraud detection has effect on taxpayer perception of tax fraud ethics, tax fairness has effect on taxpayer perception of tax fraud ethics.Keywords: tax rate, taxation technology and information, fraud, fairness, purposive sampling.